The EU S&T Co-operation with the Largest Regions of the World - Michele Genovese (Foresight and STI Governance, 2008)
The Seventh Framework Program is open to the participation of researchers from all over the world, but it presumes distinctive mechanisms of cooperation, procedures and opportunities for different groups of countries. The article presents an overview of specific programs of cooperation of EU with other world regions such as Eastern Europe and Central Asia, the countries of Western Balkans, Central and Southern Africa, the Mediterranean, Southeast Asia, and Latin America. The main challenge for their implementation are enormous differences in economic and infrastructure capabilities, laws and traditions of the countries involved. Despite the relatively small budget, according to the author, these programs are able to provide a significant contribution to the solution of many problems and to coordinate joint efforts, thus building bridges between the scientific communities.